Silver Nanoparticles: Novel Antimicrobial Agent Synthesized from an Endophytic Fungus Pestalotia sp. Isolated from Leaves of Syzygium cumini (L) - Farkanda Raheman; Shivaji Deshmukh; Avinash Ingle; Aniket Gade; Mahendra Rai (Nano Biomedicine and Engineering, 2011)
We report the extracellular synthesis of silver nanoparticles using an endophytic fungus Pestalotia sp. isolated from leaves of Syzygium cumini (L) and their antibacterial activity against human pathogenic bacteria viz. Staphylococcus aureus (ATCC-25923) and Salmonella typhi (ATCC-51812) alone and in combination with commercially available antibiotics. Detection of synthesized silver nanoparticles was carried out using UV-Visible spectrophotometer analysis, which showed a peak at 415 nm indicating the formation of nanoparticles. Further characterization includes the Fourier Transform Infra-Red spectroscopic analysis for the detection of proteins as capping agents on nanoparticles. Nanoparticle Tracking and analysis (LM 20) and TEM analysis confirmed the formation of spherical and polydispersed nanoparticles in the range of 10-40 nm having average size of 12.40 nm.Biologically synthesized silver nanoparticles showed significant antibacterial activity but their efficacy was increased in combination of antibiotics like gentamycin and sulphamethizole. Silver nanoparticles in combination with gentamycin showed maximum activity (30 mm) against S. aureus followed by sulphamethizole (25 mm). Similar results were reported in case of S. typhi where silver nanoparticles in combination with gentamycin (28 mm) showed more activity than combination of silver nanoparticles and sulphamethizole (24 mm).Biosynthetic approach using an endophytic fungus is a novel way towards the development of safe, economically viable and green method for the synthesis of silver nanoparticles and thus synthesized silver nanoparticles can be used in antibacterial formulations.